The Discourse of Animal welfare: A Case Study of JAAN (Jakarta Animal Aid Network) in Handling the Traveling Dolphins Circus - Fitri, Tasya Amalia; Riswanda, Riswanda (HK-Publishing, 2021)
Abstract Animal welfare discourse in Indonesia is rarely published on various media platforms so that public knowledge about Animal welfare is still very lacking. This study makes a case for. socio-environmental justice pf all sentient being. The study argues for the interconnectedness of socio-environmental issue with the conundrum of political aspects in, in terms of the welfare of dolphins. The study contributes to intellectual discourse on governance. Qualitative approach was chosen with respect to testing out ‘equality utilitarianism ethics to use Peter Singer’s phrase. The study indicates that the greater understanding of utilitarianism has motivated Jakarta Animal Aid Network concerning dolphins welfare, The understanding shapes awareness and public education. It then influences Indonesian government decision to stop the traveling dolphins circus that often raises socio-environmental issues especially for those who care about the rights of all sentient being.Keywords : animal welfare, dolphins, equality, ethics, governance. AbstrakWacana kesejahteraan hewan di Indonesia jarang dipublikasikan di berbagai platform media sehingga pengetahuan masyarakat tentang kesejahteraan hewan masih sangat kurang. Studi ini membuat kasus untuk. keadilan sosial-lingkungan pf semua makhluk hidup. Studi ini berpendapat untuk keterkaitan masalah sosial-lingkungan dengan teka-teki aspek politik, dalam hal kesejahteraan lumba-lumba. Studi ini berkontribusi pada wacana intelektual tentang pemerintahan. Pendekatan kualitatif dipilih sehubungan dengan menguji 'etika utilitarianisme kesetaraan untuk menggunakan frasa Peter Singer. Studi ini menunjukkan bahwa pemahaman yang lebih besar tentang utilitarianisme telah memotivasi Jaringan Bantuan Satwa Jakarta tentang kesejahteraan lumba-lumba. Pemahaman tersebut membentuk kesadaran dan pendidikan publik. Hal ini kemudian mempengaruhi keputusan pemerintah Indonesia untuk menghentikan sirkus lumba-lumba keliling yang kerap menimbulkan masalah sosial-lingkungan terutama bagi mereka yang peduli terhadap hak-hak seluruh makhluk hidup. Kata Kunci : kesejahteraan hewan, lumba-lumba, kesetaraan, etika, pemerintahan.